Performance of four wastewater treatment plants serving Ethiopia’s capital city, Addis Ababa - Haileselassie, M. M.; Mohamed, J.; Haile, Alemseged Tamiru; Hiruy, A. M.; Acharya, K.; Werner, D. (IWA Publishing, 2025)
There is an urgent need to expand wastewater treatment on the African continent. To help choose appropriate technologies for this task, we evaluated the efficiency, energy and chemical demands, and costs of four wastewater treatment plants (WWTPs). These plants represent the main wastewater treatment technologies operated by the Addis Ababa Water and Sewerage Authority (AAWSA): waste stabilization pond (WSP), anaerobic baffled reactor (ABR), up-flow anaerobic sludge blanket with trickling filter (UASB-TF), and membrane bioreactor (MBR) technologies. Principal component analysis revealed that season significantly impacts the raw and treated wastewater quality (ANOSIM, R ¼ 0.3126, p ¼ 0.001), while the type of treatment plant did not significantly affect the measured effluent characteristics (ANOSIM, R ¼ 0.1235, p ¼ 0.2000). In contrast, construction and operational costs, as well as energy and chemical demands per m3 of treated wastewater, varied starkly between the WWTPs. Total costs of wastewater treatment in 2022 ranged from $0.045 to 0.546 per m3 of wastewater treated, being 6–12 times higher for MBR compared with the other WWTP technologies. Real-world performance data as reported in this study are essential for choosing appropriate technologies that meet Africa’s wastewater treatment needs.